SEMANTIC ANALYSIS ON THE TRANSLATION OF SURAH AL-FATH (TAKEN FROM T.B IRVING’S ENGLISH TRANSLATION) - Iin Baroroh Ma'arif (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2016)
ABSTRACT In the process of communication with other person, there will be many possibilities of misunderstanding and misinterpreting of the meaning from the language we use. So that, understanding meaning is very crucial. In linguistics, we can explore our knowledge about meaning by studying semantics. This study is focused on analyzing the English translation of surah Al-Fath by T.B. Irving by using semantic theory. This study is conducted using descriptive qualitative method because the data are in the forms of sentences or words of surah Al-Fath. The result of this study shows three kinds of meaning involved in this surah namely lexical, sentential and discoursal meaning. KEYWORDS: semantics, lexical, sentential and discoursal meaning, surah al-Fath